Sugarcane leaf-derived metabolites play important role in Saccharum officinarum–Spodoptera frugiperda interactions - Liangyinan Su; Chunyu Hu; Chaoqi Wang; Baoshan Chen; Yang Zhao (Journal of Plant Interactions)
Secondary metabolites play important roles in the interactions between plants and insects. Given the complexities in these interactions, the role of secondary metabolism in plant-insect interaction is not fully understood. In this study, we identified 46 non-volatile organic compounds (NOCs) and 15 volatile organic compounds (VOCs) that differed significantly between the resistant and susceptible sugarcane lines. Phenolic acids constituted the majority of differential NOCs, with approximately 66.7% of these phenolic acids being more abundant in the susceptible line. Incorporation of phenoxyacetic acid and 4-methoxybenzaldehyde prolonged the pupal period of S. frugiperda larvae. Aromatics accounted for the largest proportion of differential VOCs in the susceptible line. Two aromatics, p-cymene and p-methoxystyrene, were found to attract S. frugiperda, with higher levels observed in the susceptible line. These results provide a basis for studying the role of NOCs and VOCs in the interaction mechanism between sugarcane and fall armyworm (S. frugiperda).